Implementasi Sistem Informasi Penerimaan Siswa Baru Berbasis Web dengan Integrasi Virtual Account untuk Optimalisasi Pembayaran (Studi Kasus: PKBM Cordova) - Muhammad Rafi Rafsanzani; Hepi Nuryadi; Yoke Lucia Renica Rehatalanit; Muryan Awaludin Awaludin (Jurnal Mahasiswa Informatika dan Desain, 2026)
Cordova Community Service Center (PKBM) East Jakarta still manages the new student admission process manually, resulting in information delays, difficulty in data retrieval, and inefficient report generation. This study aims to develop a web-based new student admission information system using the Waterfall method with PHP programming and a MySQL database, and integrating a payment system through a Virtual Account. A quantitative approach was applied through black-box testing and measuring data processing time before and after system implementation. The results showed that all 45 functional test scenarios were declared 100% valid (successful). The new system was able to reduce the new student registration time from an average of 3.5 hours (manually) to 8.5 minutes via the website (95.9% efficiency). The time to create new student admission reports decreased from 60 minutes to 2.5 minutes (95.8% efficiency). The implementation of the Virtual Account successfully reduced the payment recording error rate from 18.4% (manually) to 0% (automatically verified by the system). In addition, access to information by student guardians increased with an average access time of 2.3 seconds per page. In conclusion, this web-based new student admissions information system has proven effective in increasing registration efficiency, payment data accuracy, and ease of report creation at PKBM Cordova..